The Role of Self-efficacy and Communication Skills of Researchers to Organizational Climate at Research Center X (Peran Efikasi Diri dan Kemampuan Komunikasi Peneliti Terhadap Iklim Organisasi di Pusat Penelitian X) - Mia Rahma Romadona (BBPSDMP KOMINFO MAKASSAR, 2017)
Many previous studies explain that self-efficacy can directly support individual and organizational productivity, the R & D or research center as well as other organizations also have performance targets that must be achieved. Many cases of R & D is the difficulty of managing human resources researcher with the characteristics of creative people to be able to support the productivity of individuals and institutions. Self efficacy and communication skills good organization on the researcher is required to support the achievement of the objectives of R & D. The purpose of this study is to measure the level of self-efficacy that can impact the communication skills of researchers that will affect productivity with a conducive organizational climate. The method used in the study using case studies sector in R & D with a quantitative approach to measure the level of self-efficacy and to explain and interpret qualitative communication skills and self-efficacy on the researcher at the research center X. The result is the level of self efficacy of each researcher based on the level of functional position has a very significant difference. Self efficacy in high researchers is not accompanied by the communication skills of the organization, so that the organization's climate becomes less conducive to sharing knowledge or information. As for personal communication researchers do not have constraints and even good enough to be able to communicate. It illustrates that high self-efficacy but poor communication skills will make the productivity of the organization be less than the optimum.Banyak kajian sebelumnya yang menjelaskan bahwa efikasi diri dapat secara langsung mendukung produktivitas individu dan organisasi, untuk itu sebagaimana organisasi lainnya litbang atau pusat penelitian juga memiliki target yang harus dicapai. Salah satu kasus litbang adalah kesulitan untuk mengelola SDM penelitinya dengan karakteristik creative people untuk dapat mendukung produktivitas individu ataupun lembaga. Efikasi diri dan keterampilan komunikasi organisasi yang baik pada peneliti dibutuhkan untuk dapat mendukung pencapaian tujuan litbang. Tujuan kajian ini adalah mengukur tingkat efikasi diri yang dapat memberikan dampak pada keterampilan komunikasi peneliti yang akan berdampak produktivitas dengan iklim organisasi yang kondusif. Metode yang digunakan dalam kajian ini menggunakan studi kasus di suatu litbang dengan pendekatan kuantitatif untuk mengukur tingkat efikasi diri dan kualitatif untuk menjelaskan dan menginterpretasikan keterampilan komunikasi dan efikasi diri pada peneliti di pusat penelitian X. Ada pun hasilnya adalah tingkat efikasi diri setiap peneliti berdasarkan jenjang jabatan fungsionalnya memiliki perbedaan yang sangat signifikan. Efikasi diri pada peneliti yang tinggi tidak dibarengi dengan keterampilan komunikasi organisasinya, sehingga iklim organisasi menjadi kurang kondusif untuk melakukan sharing knowledge ataupun informasi. Adapun dalam komunikasi personal peneliti tidak memiliki kendala dan bahkan cukup baik untuk dapat berkomunikasi. Hal itu menggambarkan bahwa efikasi diri yang tinggi namun keterampilan komunikasi yang kurang baik akan menjadikan produktivitas organisasi menjadi kurang optimum.